Doing Internet research : critical issues and methods for examining the Net - Jones, Steve, 1961- (Sage Publications, 1999)
'Doing Internet Research' examines the ways in which the Internet has commanded the public imagination and discusses the methodological issues that arise when one tries to study and understand the social processes occurring within the Internet.